2006
DOI: 10.1016/j.cmet.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory and metabolic defects in Huntington's disease transgenic mice implicate PGC-1α in Huntington's disease neurodegeneration

Abstract: Huntington's disease (HD) is a fatal, dominantly inherited disorder caused by polyglutamine repeat expansion in the huntingtin (htt) gene. Here, we observe that HD mice develop hypothermia associated with impaired activation of brown adipose tissue (BAT). Although sympathetic stimulation of PPARgamma coactivator 1alpha (PGC-1alpha) was intact in BAT of HD mice, uncoupling protein 1 (UCP-1) induction was blunted. In cultured cells, expression of mutant htt suppressed UCP-1 promoter activity; this was reversed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
468
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(501 citation statements)
references
References 59 publications
26
468
3
4
Order By: Relevance
“…As a result, the transcription of ROS-scavenging enzymes is down-regulated, and the concentration of ROS in the neurons increases. These important observations were reinforced by the finding that striatal neurons from HD knock-in mice were resistant to 3-NPA when expressing exogenous PGC-1␣ (22).…”
Section: Huntington Disease (Hd)mentioning
confidence: 68%
“…As a result, the transcription of ROS-scavenging enzymes is down-regulated, and the concentration of ROS in the neurons increases. These important observations were reinforced by the finding that striatal neurons from HD knock-in mice were resistant to 3-NPA when expressing exogenous PGC-1␣ (22).…”
Section: Huntington Disease (Hd)mentioning
confidence: 68%
“…Whether the brain-specific isoforms have functional activation domains remains to be determined. Interestingly, the newly identified promoter that mediates the transcription of these brain PGC-1α isoforms is located in a genomic region associated with age of onset of Huntington's disease [41], a disease that has been linked to altered PGC-1α function [42][43][44]. …”
Section: Where Do We Start? Multiple Origins For Pgc-1α Transcriptsmentioning
confidence: 99%
“…First, HD is attributable to an expanded glutamine repeat stretch in the protein huntingtin (mhtt). Among its many cellular manifestations, mhtt leads to transcriptional repression of many genes, including those controlling adaptation to low mitochondrial energy charge such as PPARg coactivator 1a (PGC-1a) (7,8,35). Indeed, recent studies have shown that germline deletion of PGC-1a leads to striatal degeneration similar in localization and behavioral manifestations to HD (17); by contrast, PGC-1a overexpression via lentiviral delivery in vivo prevents striatal degeneration attributable to transgenic expression of mhtt (8).…”
mentioning
confidence: 99%